The Three Stooges funniest moments.II II - Oliveri, Sandy; Three Stooges (Comedy team); Film Shows, Inc.; GoodTimes Entertainment (Firm); GoodTimes DVD (Firm) (New York, N.Y. : GoodTimes DVD, 2000)
More glimpses of Moe Howard, Larry Fine and Curly Joe DeRita in color which were shot in 1965 as live-action scenes for The New Three Stooges cartoon show.
"More mirthful moments with the Stooges in full color"-- Container.
Executive producers, Ken Cayre, Stan Cayre, Joe Cayre ; creative consultant, Ken Cayre.
The Three Stooges.
DVD ; all regions ; standard full frame (1.33:1) ; single layer ; mono. ; Dolby digital.
Keywords: Three Stooges films; Television comedies